2019
DOI: 10.1002/evl3.131
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary lability inHoxcluster structure and gene expression inAnolislizards

Abstract: Hox genes orchestrate development by patterning the embryonic axis. Vertebrate Hox genes are arranged in four compact clusters, and the spacing between genes is assumed to be crucial for their function. The genomes of squamate reptiles are unusually rich and variable in transposable elements (TEs), and it has been suggested that TE invasion is responsible for the Hox cluster expansion seen in snakes and lizards. Using de novo TE prediction on 17 genomes of lizards and snakes, I show that TE content of Hox clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Observations from these new assemblies have provided fresh insights into core biological processes. For example, our understanding of recombination 4 , repetitive genetic elements 5,6 , chromosome evolution 7-9 and dosage compensation 4,10,11 have all been fundamentally amended due to results made possible by recent genome assemblies of non-traditional model species.…”
Section: Introductionmentioning
confidence: 99%
“…Observations from these new assemblies have provided fresh insights into core biological processes. For example, our understanding of recombination 4 , repetitive genetic elements 5,6 , chromosome evolution 7-9 and dosage compensation 4,10,11 have all been fundamentally amended due to results made possible by recent genome assemblies of non-traditional model species.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, as was found in diverse mammalian cell types [ 64 , 65 ], some transposable elements included in genes, such as SINEs and LINEs [ 66 , 67 ], might participate in the splicing of the precursor of mRNA (pre-mRNA) and in the formation of non-coding circular RNAs [ 68 , 69 ], that function as efficient miRNA sponges [ 70 ], thus diminishing the effect of miRNA on transcriptional and post-transcriptional levels of regulation of gene expression [ 71 ]. The functionality of transposons in the Hox cluster became more plausible with the discovery of a correlation between the accumulation of mobile elements and the level of Hox genes’ expression during development in Anolis lizards [ 20 ]. However, so far, it is unclear what part of transposons remains functional, since most of them are considerably degenerated.…”
Section: Resultsmentioning
confidence: 99%
“…However, comparison between Hox clusters of mouse, chicken, frog and green anole demonstrated atypical enlarged Hox clusters in the anole lizard with a massive accumulation of transposable elements in intergenic space [ 12 ]. A recent study showed that mobile elements accumulation correlates with alterations in Hox genes expression during development in Anolis lizards and can possibly contribute to their speciation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Embryos were transferred to methanol through a dilution series in PBS and stored at −20°C. In situ hybridization was performed as previously described ( 51 ). Expression patterns were documented using a Nikon stereo microscope (Nikon SMZ18) with the imaging software NIS-Elements BR 5.02.00.…”
Section: Methodsmentioning
confidence: 99%